Creating a Niche for Performance Auditing in the Public Sector: Utilizing Integrated Compliance, Efficiency and Effectiveness Reporting - Fayyaz, Aamir (Journal of Pakistan Administration, 2024)
Supreme Audit Institutions (SAIs), being public sector audit organizations, usually derive their mandate from the highest law of the land. They perform three broad types of audits- financial, compliance and performance audits. Each audit type has a specific purpose and its conduct is guided by the applicable legal framework, auditing principles and standards. In the context of Pakistan, while the SAI conducts all three types of audits, in terms of overall audit coverage, the share of performance audit is generally on the lower side compared with financial and compliance audits. One reason for this could be the practice of conducting performance audits as stand-alone audit assignments, separately, and distinct from financial and compliance audits. Performance audit cycle is entirely different from other types of audits and is generally more resource-intensive. While a significant number of entities get audited from financial and compliance perspective every year, not all get a chance to benefit from performance audits. Since the latter is generally considered to be more holistic and wide-ranging, compared with other audit types, there is a dire need to increase its coverage in the overall audit mix. Many strategies can be adopted to accomplish this task. This paper proposes that audit cycle for performance audits may be combined with that of compliance audits. Since the latter are the mainstay of public audits, their integration with performance audits, will give a boost to the coverage of the latter. The combined reports, covering compliance, efficiency and effectiveness aspects, will provide a more fulfilling and rich experience to the stakeholders, contributing to enhanced transparency and accountability for the entrusted resources.
Keywords: Compliance Audit; Integrated Audit; INTOSAI; Performance Audi; Supreme Audit Institutions (SAIs)